AUTHENTICATION EFFECTIVENESS INFORMATIVE BOARD (Perner's Contacts, 2011)
This paper deals with the psychological elements of traffic calming. In particular, deals with informative boards. With this type of security measure is not proven its effectiveness, so this paper also deals with the possibility of detecting the effectiveness of informational boards..
Keywords: traffic calming; speed measurement; safety of transport